Concomitant occurrence of primary renal non-Hodgkin lymphoma and a colon cancer: A rare case report. Issue 10 (March 2019) - Li, Ji; Zou, Yabin; Wang, Bin; Meng, Xiangwei; Sun, Xun
Abstract: Rationale: Primary renal lymphoma (PRL) is a rare malignancy due to the absence of lymphatic tissues in the kidney, and patients with PRL have been reported to have a poor prognosis due to its rapid invasiveness and limited treatment strategies. Colon cancer is the third most common cancer, and has a high mortality rate. Both malignant diseases predominantly affected elderly men; however, a case with concomitant occurrence of the 2 cancers is extremely rare. Patient concerns: A 78-year-old male patient with abdominal pain came to our hospital. Computed tomography (CT) indicated malignant masses in the left kidney, left adrenal gland, and the lower part of the descending colon. Diagnoses: PRL and colon cancer were diagnosed based on pathological examinations. Interventions: The patient was treated with laparoscopic radical nephrectomy and laparoscopic radical resection of colon cancer. Outcomes: The patient was then transferred to the intensive care unit (ICU) because of poor condition after surgery. He died 3 months after discharge without receiving any other treatment. Lessons: It is worth thinking about whether surgery was reasonable for elderly patients with double malignancies, or palliative treatment to improve the quality of life was more meaningful. This case also contributes to the understanding of the 2 malignancies and highlights the need to pay more attention to patients with multiple primary malignant neoplasms (MPMNs), explore genetic features, and investigate treatments with more survival benefits.